Anorthosite and associated plutons, southern Nain complex, Labrador - Wiebe, Robert A. (Canadian Journal of Earth Sciences, 1978)
Plutonic rocks in a southern area of the Nain anorthosite complex consist of leuconorite, anorthosite, granite, and subordinate diorite. An older anorthosite intrusion (CI < 10) has been invaded and broken up by an extensive leuconorite intrusion (CI = 15). Ferrodiorite occurs as small bodies within or adjacent to the leuconorite and is a late stage differentiate of leuconorite, Large granitic plutons of separate crustal origin were emplaced prior to complete solidification of the leuconorite. Where these intrusions invaded leuconorite a marginal hybrid (diorite–granite) zone of heterogeneous matrix developed with chilled pillows of residual magma (mainly ferrodiorite) filter-pressed from the leuconorite. Chilled leuconorite dikes indicate that the parent magma of one leuconorite intrusion was approximately equivalent to its average composition. The older anorthosite body most probably represents a concentration of plagioclase crystals from a different magma; deformation of plagioclase crystals suggest that the mechanism of concentration was filter pressing.